COMPLEX CHARACTERISTICS OF PATIENTS WITH COXARTHROSIS IN IRKUTSK REGION - V. A. Koryak; A. I. Sidorov; O. M. Chernikova (Acta Biomedica Scientifica, 2012)
Coxarthorosis is a degenerative-dystrophic disorder affecting all layers of population with increasing sickness rate among adult people. Coxarthoris is characterized by steadily progressive course leading patients to disability without ability of self-service. Closer attention of all kinds of medical workers is necessary in diagnostics and. rendering of all kinds of assistance available for this category of patients: not only qualified, medical attention, but also help in social rehabilitation.